Dynamic Validation of OCL Constraints with mOdCL - Roldan, Manuel; Durán, Francisco (Electronic Communications of the EASST, 2011)
This paper presents mOdCL, a Maude based evaluator of OCLexpressions and validator of OCL constraints. Given its OCLexpression evaluator, the use of execution strategies allows mOdCL, not only validating invariant constraints on concrete system states, but also dynamically validating invariants and pre- and post-conditions on the successive states obtained during systemexecution.